The Relationships between Family Support, Age, and Gender with Quality of Life in Chronic Kidney Failure Patients at Dr. Moewardi Surakarta Hospital - Rizky Nur Aprilianti Amalia; Didik Gunawan Tamtomo; Bhisma Murti (Masters Program in Public Health, 2024)
Background: Chronic kidney failure (CKD) is a non-communicable disease in which kidney function begins to decline progressively in a matter of months or even years and can affect the patient's quality of life. The purpose of this study is to determine the effect of family support, gender and age on the quality of life of patients with chronic kidney failure at Dr. Moewardi Hospital Surakarta.Subjects and Method: This study used a cross-sectional design conducted at Dr. Moewardi Surakarta Hospital in June 2024. The target population of the study was 920 patients with chronic kidney failure at Dr. Moewardi Hospital Surakarta. A total of 200 study subjects were selected using simple random sampling. The dependent variables are family support, age, and gender. The independent variable is quality of life. The study instruments used were questionnaires and checklists and the data was analyzed using multiple linear regression analysis and processed using Stata 13.Results:There was a statistically significant relationship between family support and quality of life in patients with chronic kidney failure. Each increase in family support score by one unit will be followed by an improvement in the quality of life of chronic kidney failure patients by 0.31 units (b = 0.31; CI 95% = 0.42 to 0.57; p = 0.023). Statistically, there is a significant relationship between age and quality of life of patients with chronic kidney failure. Each one-year increase in age will be followed by an improvement in the quality of life of chronic kidney failure patients by 0.02 units (b = 0.02; CI 95% = 0.05 to 0.38; p = 0.012). There is a very small difference in quality of life between female and male chronic kidney failure patients. Female patients with chronic kidney failure were 0.01 years lower than men, but the difference was statistically very insignificant (b = -0.80; CI 95% = -0.51 to 0.50; p = 0.975).Conclusion: There was a positive relationship between family support and age and quality of life in patients with chronic kidney failure and there was no significant difference by gender between women and men.